FACTORS AFFECTING WILLINGNESS TO LENDFINTECH BASED ON PEER TO PEER LENDING WITH THE LEVEL OF PLATFORM TRUST AS AN INTERVENING VARIABLE - Arief Rachman; Wisnu Mawardi (Jurnal Apresiasi Ekonomi, 2024)
Fintech P2P Lending was introduced in Indonesia in 2015 and along with technological advances, the P2P Lending industry experienced rapid development. This P2P Lending service connects lenders with borrowers to agree on lending and borrowing transactions. The aim of this research is to analyze the factors that influence the willingness to lend to fintech based on peer to peer lending with the level of trust in the platform as an intervening variable.The population from data collected from the Financial Services Authority Statistics is 158,366 bank accounts. Determining the sample using the Slovin technique, from the calculation results it was obtained that there were 99 rounded up to 100 samples who had been lenders from P2P lending platforms. The research results show that regulatory protection has a positive (0.265) and significant (0.001 < 0.05) effect on trust in the platform. Security guarant ees have a positive (0.584) and significant (0.000 < 0.05) effect on trust in the platform. Regulatory protection has a positive (0.203) and significant (0.030 < 0.05) effect on willingness to lend. Security guarantees have a positive (0.256) and significant (0.039< 0.05) effect on willingness to lend. Trust in the platform has a positive (0.388) and significant (0.004< 0.05) effect on willingness to lend. Regulatory protection has a significant effect (0.040< 0.05) on willingness to lend mediated by trust in the platform. Security guarantees have a significant effect (0.008< 0.05) on willingness to lend mediated by trust in the platform.Keywords: Regulatory Protection, Security Guarantee, Platform Trust, Willingness To Lend